WOMENS LANGUAGE FEATURES USED BY THE FEMALE CHARACTERS IN WONDER WOMAN MOVIE - DEWI ANJANI, LIYA (LANGUAGE HORIZON, 2019)
This study was conducted in a descriptive qualitative analysis. The descriptive qualitative was used during the research, because this study used all the female characters utterances in Wonder Woman movie. It means that the research focus in narrowed down only gradually and the analytic categories or concept are defined during the process of the research.The data are presented from the form of word and the utterances of female characters and other the interlocutor?s in a certain scene in ?Wonder Woman?. The data was analyzed based on Lakoff theory. Moreover, this part consist of the result of the types of women?s language features, reasons why they used it, and impact toward the interlocutors which is used by female characters and the interlocutor?s in the movie ?Wonder Woman?. There are several types of speech features that found in this study. The writer found 13 data about female characters and the interlocutor?s utterances that consist of the speech features. From the data that has been taken, all data will be analyzed. The data were also already being sorted out from the movie ?Wonder Woman? because the amount of the data.